Influence of Wood-Based Biomass Ash Admixing on the Structural, Mechanical, Hygric, and Thermal Properties of Air Lime Mortars - Pavlíková, Milena; Zemanová, Lucie; Pokorný, Jaroslav; Záleská, Martina; Jankovský, Ondřej; Lojka, Michal; Pavlík, Zbyšek (Materials (Basel, Switzerland), 2019)
Mechanically-activated wood-based biomass ash (WBA) was studied as a potential active admixture for design of a novel lime-pozzolan-based mortar for renovation purposes. The replacement ratio of lime hydrate in a mortar mix composition was 5%, 10%, and 15% by mass. The water/binder ratio and the sand/binder ratio were kept constant for all examined mortar mixes. Both binder constituents were characterized by their powder density, specific density, BET (Brunauer-Emmett-Teller), and Blaine specific surfaces. Their chemical composition was measured by X-ray fluorescence analysis (XRF) and mineralogical analysis was performed using X-ray diffraction (XRD). Morphology of WBA was investigated by scanning electron microscopy (SEM) and element mapping was performed using an energy dispersive spectroscopy (EDS) analyzer. The pozzolanic activity of WBA was tested by the Chapelle test and assessment of the Portlandite content used simultaneous thermal analysis (STA). For the hardened mortar samples, a complete set of structural, mechanical, hygric, and thermal parameters was experimentally determined. The mortars with WBA admixing yielded similar or better functional properties than those obtained for traditional pure lime-based plaster, pointing to their presumed application as rendering and walling renovation mortars. As the Chapelle test, STA, and mechanical test proved high pozzolanity of WBA, it was classified as an alternative eco-efficient low-cost pozzolan for use in lime blend-based building materials. The savings in CO2 emissions and energy by the use of WBA as a partial lime hydrate substitute in mortar composition were also highly appreciated with respect to the sustainability of the construction industry.
Keywords: lime-pozzolan renovation mortars; environmental assessment; wood-based biomass ash; pozzolanic activity; industrial waste; functional properties; binder physical and chemical analyses